2021
DOI: 10.1590/1982-0216/202123312920
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation in speech-language-hearing therapy: a profile of professional practice and the level of information of Brazilian speech-language-hearing therapists

Abstract: Purpose: to know the profile of Brazilian speech-language-hearing (SLH) therapists and their level of information on the use of low-level laser photobiomodulation. Methods: an observational, cross-sectional, quantitative study conducted with a self-administered online questionnaire related to the professional education, work, and knowledge of SLH therapists on low-level laser photobiomodulation. Two hundred sixty-one speech-language-hearing therapists of both sexes participated in the research. The data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(37 reference statements)
1
3
0
3
Order By: Relevance
“…Along with the rather young sample (mean of 40 years old) and the various postgraduate degrees, this suggests an effort to modernize their work in this field. It also indicates that most SLH therapists who work with oralmotor function are young adults -which agrees with other studies on complementary strategies associated with myofunctional therapy (such as photobiomodulation), in which the mean ages were 43 15 and 38 years old 16 .…”
Section: Discussionsupporting
confidence: 88%
“…Along with the rather young sample (mean of 40 years old) and the various postgraduate degrees, this suggests an effort to modernize their work in this field. It also indicates that most SLH therapists who work with oralmotor function are young adults -which agrees with other studies on complementary strategies associated with myofunctional therapy (such as photobiomodulation), in which the mean ages were 43 15 and 38 years old 16 .…”
Section: Discussionsupporting
confidence: 88%
“…In this study, it was observed, through the performance of exercises for the stomatognathic functions and mainly aimed at the rehabilitation of facial mime, which had as objectives the gain of tonus and strength of the oral musculature. 36,37 According to the literature and observed in the reported case, photobiomodulation [38][39][40][41][42] and electrostimulation [43][44][45] associated with orofacial motor exercises 38,41,42,44 promoted positive results in control of saliva flow and ensure greater oromiofacial mobility, accelerating strength gain, maintaining fatigue levels and improving muscle performance. There are still limitations in the literature that do not allow a deeper understanding of the issue, as few articles related speech therapy rehabilitation in patients diagnosed with Tapia´s Syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Este dado sugere, alinhado com a idade mais jovem da amostra, com média de 40 anos, que existe uma busca por modernização nesta área, nos diversos graus de aprofundamento ao nível de pós-graduação. Indica também que os fonoaudiólogos atuantes da área de MO são, em sua maioria, de adultos jovens, semelhante a outros estudos sobre estratégias complementares associadas à terapia miofuncional, como o fotobiomodulação, em que as médias de idades encontradas foram 43 anos 15 e 38 anos 16 .…”
Section: Discussionunclassified